110 degrees in the waterbag : a history of life, work and leisure in Leonora, Gwalia and the northern goldfields - Layman, Lenore; Fitzgerald, Criena (Western Australian Museum, 2012)
The goldfields have been a powerful influence on both Australian and Western Australian history. Gold has driven development in many parts of Australia. A great number of family lives have been shaped by migration to and from the fields. Reminiscences, and family and local histories have produced powerful and oft-repeated narratives. This book moves beyond the oft-told. It tells of Aboriginal history, of people who have 'always been here, and we always will be here'. Women's and children's lives are explored as well as those of prospectors and miners, the settlement of 'Afghans' and the story o.